Long-term outcomes combined minimally invasive laser surgical technique for local rhegmatogenous retinal detachment - A.V. Doga; D.O. Shkvorchenko; L.A. Kryl; M.R. Taevere; D.A. Buryakov (РМЖ "Клиническая офтальмология")
A.V. Doga, D.O. Shkvorchenko, L.A. Kryl, M.R. Taevere, D.A. Buryakov S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Moscow, Russian Federation Aim: to evaluate the long-term clinical efficacy of the combined (laser plus surgical) minimally invasive technique for rhegmatogenous retinal detachment (RRD). Patients and Methods: treatment results of 41 patients (41 eyes) with local RRD resulting from horseshoe retinal tear were analyzed. All patients underwent wide-field optical coherence tomography (OCT) to localize and measure pathological vitreoretinal adhesions at the site of retinal tear. The next step was a combined laser surgical procedure that included Nd: YAG dissection of pathological vitreoretinal adhesion zone, pneumatic retinopexy (10% C3F8), and barrier laser retinal photocoagulation (LRP) after reattachment. Postoperatively, eye exams were performed after 3 and 7 days, 3, 6, 12, 18, and 24 months. Results: complete reattachment was achieved in 38 patients (92.7%) on day 2 or 3. No reattachment was seen in three patients (7.3%); of them, subretinal gas migration was observed in two patients (4.9%), and partial reattachment was detected in one patient (2.4%) with pseudophakia. Recurrent RRD occurred in 3 patients (7.9%) because of new inferior retinal breaks. In four patients (10.5%), postoperative wide-field OCT of the area of the initial retinal tear performed after reattachment revealed additional pathological vitreoretinal adhesions in the adjacent areas (that were not identified preoperatively). These patients underwent additional LRP around the areas of pathological vitreoretinal adhesions. No recurrent RRDs were seen during follow-up. Conclusion: combined minimally invasive laser surgical technique for local PPDs demonstrated high efficacy (92.7%). This technique was the effective in local retinal detachment resulting from a single superior horseshoe retinal tear in patients with crystalline lens. In some cases, pseudophakia is a technical obstacle to this procedure. Postoperative wide-field OCT is recommended to detect additional pathological vitreoretinal adhesions and to perform LRP around them to reduce the risks of recurrent RRDs greatly. Keywords: rhegmatogenous retinal detachment, optical coherence tomography, Nd: YAG laser retinotomy, vitreoretinal traction. For citation: Doga A.V., Shkvorchenko D.O., Kryl L.A. et al. Long-term outcomes combined minimally invasive laser surgical technique for local rhegmatogenous retinal detachment. Russian Journal of Clinical Ophthalmology. 2021;21(2):63–68. DOI: 10.32364/2311-7729-2021-21-2-63-68.